Communicative planning as counter-power. Issue 3 (3rd July 2017) - Elling, Bo
ABSTRACT: This article presents a theory of communicative planning in which the power of citizens is conceived as a resource in the promotion of long-term planning against the short-term interests of investors in public planning. Its point of departure is the depiction of three planning paradigms – traditional synoptic, incremental and participatory planning – and a critical discussion of different theories within the latter. In the light of this, it is argued that, in practice, planning authorities most often regard public participation as a problem, rather than as a potential. The article dismisses this conception and (a) conceptualizes planning on the basis of a Habermasian theory of communicative action and power, (b) shows that the participation of citizens is necessary to secure the inclusion of ethical and aesthetic rationalities in the planning process, and also that (c) citizens may constitute a counterpower to short-term investor interests in planning by (d) strengthening the respect for long-term solutions and the common good. This becomes a structural necessity when it comes to securing sustainability and democratic justice in planning. The article conceptualizes the difference between planning and politics, since in the former, power is constituted in the actual process, not given in advance.